Pectin Methylesterase Isoforms in Tomato (Lycopersicon esculentum) Tissues (Effects of Expression of a Pectin Methylesterase Antisense Gene). - Gaffe, J. (1994)
We have identified two major groups of pectin methylesterase (PME, EC 3.1.1.11) isoforms in various tissues of tomatoes (Lycopersicon esculentum). These two groups exhibited differential immuno-cross-reactivity with polyclonal antibodies raised against tomato fruit PME or flax callus PME and differences in their accumulation patterns in tissues of wild-type and transgenic tomato plants expressing a PME antisense gene. The group I isoforms with isoelectric points (pls) of 8.2, 8.4, and 8.5 are specific to fruit tissue, where they are the major forms of PME activity. The group II PME isoforms, with pl values of 9 and above, are observed in both vegetative and fruit tissues. The group I isoforms cross-react with polyclonal antibodies raised to a PME isoform purified from fruit, whereas the group II isoforms cross-react with antibodies to a PME purified from flax callus. Expression of a fruit-specific PME anti-sense gene impairs accumulation of the group I PME isoforms, with no apparent effect on the accumulation of the group II PME isoforms. The absence of any noticeable effects on growth and development of transgenic plants suggests that the group I PME isoforms are not involved in plant growth and development and may play a role under special circumstances such as cell separation during fruit ripening.